Identification and Expression Analysis of Long Non-coding RNA in Large Yellow Croaker (Larimichthys crocea) in Response to Cryptocaryon irritans Infection - Zhang, Xinyi; Zhou, Tao; Chen, Baohua; Bai, Huaqiang; Bai, Yulin; Zhao, Ji; Pu, Fei; Wu, Yidi; Chen, Lin; Shi, Yue; Ke, Qiaozhen; Zheng, Weiqiang; et al. (Frontiers in Genetics, 2020)
Large-scale transcription studies have revealed numerous lncRNAs (long non-coding RNAs). LncRNAs have been proposed to participate in the regulation of a diverse range of biological processes, including transcriptional regulation. Although lncRNAs have attracted increasing attention, the studies in large yellow croaker (Larimichthys crocea) are still rare and lack of systematic analysis. In this study, 101 RNA-seq datasets varied in ages, sexes, and tissues were retrieved from the NCBI database to generate a comprehensive catalog of large yellow croaker transcriptome database. A set of 14,599 high-confidence lncRNAs from 13,673 loci were identified and characterized. Furthermore, RNA-seq datasets obtained from the infection of C. irritans were employed to investigate the differential expression pattern of lncRNAs and analyze potential biological functions. A total of 77 differentially expressed lncRNAs targeting to 567 protein-coding genes were identified by using expression analysis. Several immune genes, including TLR5, CD2AP, and MMP9 were highlighted. With GO enrichment and KEGG pathway analysis, the immune-related terms or pathways were enriched. This study created a comprehensive dataset of lncRNAs for large yellow croaker, which would be helpful for the researches of functional roles of lncRNAs in large yellow croaker.